In Vitro Effects of Yeast Extract and Indole-3-Acetic Acid on Shoot Emergence and Height in Mas Kirana Banana - Samanhudi Samanhudi; Retna Bandriyati Arniputri; Sri Hartati; Iswahyudi Iswahyudi; Dewi Selvia Maulida Saputri (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2025)
Mas Kirana banana (Musa sp.) is a superior local variety from Lumajang, East Java, valued for its favorable fruit size and consumer preference. Conventional propagation of this variety is limited due to its low production of saplings (2–3 per clump), making large-scale cultivation inefficient. Tissue culture techniques offer an alternative approach to accelerate propagation. This study aimed to evaluate the effects of yeast extract and indole-3-acetic acid (IAA) on the in vitro growth of Mas Kirana banana explants. The experiment was arranged in a factorial completely randomized design (CRD) with two factors: yeast extract at four concentrations (0, 400, 800, and 1200 mg L⁻¹) and IAA at four concentrations (0, 0.75, 1.5, and 2.25 ppm). Growth responses were assessed based on shoot emergence, shoot height, root development, and leaf formation. Yeast extract significantly affected shoot emergence time; however, its effect was inhibitory rather than promotive. The control (0 mg L⁻¹) produced the fastest emergence (11 DAP), whereas higher yeast concentrations (400–1200 mg L⁻¹) delayed emergence to 13–22 DAP.. IAA significantly influenced shoot height, with the best performance at 1.5 ppm, while other growth parameters were not significantly affected. These findings indicate that the effectiveness of yeast extract and IAA is highly concentration-dependent, and their roles in improving micropropagation of Mas Kirana banana require further optimization. This study provides baseline information to support the development of more efficient tissue culture protocols for large-scale propagation of this important local variety.